PENGEMBANGAN MEDIA DIGITAL SITUS CANDI JAGO DALAM MENINGKATKAN HASIL BELAJAR MAHASISWA SEJARAH IKIP BUDI UTOMO MALANG - Ferdinan Bashofi; Suheri Widianto (IKIP Budi Utomo Malang, 2018)
The purpose of this research is to design the learning media of Indonesian cultural history, and to describe the effect of media usage on student learning outcomes. This research is a development research using Sugiyono model, while tehadap learning result using pseudo experiment to know effectiveness to result learn. The findings in the field show there are 4 relics of the temple building from the Hindu-Buddhist era and which is used as a model is Jago temple. The result of validity test of learning media is expressed well by validator with obtained validation result: 75,5% from media expert which mean included in criterion good enough, while from material expert equal to 80% good category. Result of data of questionnaires validation of practitioner 1 validation toward learning media obtained percentage 85%. Learning media developed after tested try to get good response from students with percentage of 81% with good category. Learning media developed effectively because after tested, and obtained the results: (1) the average learning outcomes in the form of absorption of material comprehension, the number of students who complete learning as much as 28 of 29 students with students’ learning completeness classically is 96.5% average value 84.48, (2) students’ experimental class learning outcomes are better than control class, (3) there is statistically significant difference or significant use of digital learning media of jago temple site to increase student learning outcomes.